The Bunyavirales: The Plant-Infecting Counterparts - Kormelink, Richard; Verchot, Jeanmarie; Tao, Xiaorong; Desbiez, Cecile (Viruses, 2021)
Negative-strand (-) RNA viruses (NSVs) comprise a large and diverse group of viruses that are generally divided in those with non-segmented and those with segmented genomes. Whereas most NSVs infect animals and humans, the smaller group of the plant-infecting counterparts is expanding, with many causing devastating diseases worldwide, affecting a large number of major bulk and high-value food crops. In 2018, the taxonomy of segmented NSVs faced a major reorganization with the establishment of the order Bunyavirales. This article overviews the major plant viruses that are part of the order, i.e., orthospoviruses (Tospoviridae), tenuiviruses (Phenuiviridae), and emaraviruses (Fimoviridae), and provides updates on the more recent ongoing research. Features shared with the animal-infecting counterparts are mentioned, however, special attention is given to their adaptation to plant hosts and vector transmission, including intra/intercellular trafficking and viral counter defense to antiviral RNAi.